Thermoregulatory responses to cycling with and without a helmet - Sheffield-Moore, M.; Short, K. R.; Kerr, C. G.; Parcell, A. C.; Bolster, D. R.; Costill, D. L. (Medicine & Science in Sports & Exercise, 1997)
This study examined the effects of wearing a helmet on selected body temperatures and perceived heat sensation of the head and body while cycling in a hot-dry (D) (35 degrees C, 20% relative humidity (RH) and hot-humid (H) (35 degrees C, 70% RH) environment. Ten male and four female cyclists (mean +/- SD: males = age 27 +/- 7 yr, peak O2 uptake (VO2) 4.10 +/- 0.54 L.min-1; females = age 26 +/- 3 yr, peak O2 uptake (VO2) 3.08 +/- 0.49 L.min-1) performed four randomized 90-min cycling trials at 60% of peak VO2 both with (HE) and without (NH) a commercially available cycling helmet in both D and H environments. VO2, core (Te), skin (Tsk), and head skin temperatures, heart rate (HR), rating of perceived exertion (RPE), and perceived thermal sensation of head (TSH) and body (TSB) were measured throughout exercise. For all measured variables, no significant difference was evident between HE and NH. However, Tc, Tsk, and mean head skin temperatures were higher (P < 0.001) in H than D. Likewise, RPE, TSH, TSB (P < 0.001), and sweat rates (H = 1.33 +/- 0.32, D = 1.14 +/- 0.23 L.h-1) (P < 0.01) were higher in H versus D. Results indicate that use of a commercially available cycling helmet while riding in a hot-dry or hot-humid environment does not cause the subjects to become more hyperthermic or increase perceived heat sensation of the head or body.